2018
DOI: 10.1302/2046-3758.712.bjr-2018-0035.r1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plate design, bridging span, and fracture healing on the performance of high tibial osteotomy plates

Abstract: ObjectivesOpening wedge high tibial osteotomy (HTO) is an established surgical procedure for the treatment of early-stage knee arthritis. Other than infection, the majority of complications are related to mechanical factors – in particular, stimulation of healing at the osteotomy site. This study used finite element (FE) analysis to investigate the effect of plate design and bridging span on interfragmentary movement (IFM) and the influence of fracture healing on plate stress and potential failure.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 52 publications
2
37
0
Order By: Relevance
“…While the authors acknowledged this confounding factor, we believe that these results have been misinterpreted in the literature. 11,13 We believe the fracture conditions modelled by Stoffel and colleagues 6 are unlikely to be realistic for a clinical situation. Eccentric axial loading producing only tension bending in a small gap, transverse fracture without concurrent torsional and compressive loads would be an unlikely clinical scenario.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…While the authors acknowledged this confounding factor, we believe that these results have been misinterpreted in the literature. 11,13 We believe the fracture conditions modelled by Stoffel and colleagues 6 are unlikely to be realistic for a clinical situation. Eccentric axial loading producing only tension bending in a small gap, transverse fracture without concurrent torsional and compressive loads would be an unlikely clinical scenario.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are consistent with other studies that demonstrated greater construct stiffness with shorter working lengths. [6][7][8][9][10][11]31 Plate strain was determined at twelve ROI using digital image correlation for both plate types under compression bending and torsion. At no ROI, mean plate strain was reduced by increasing working length under either load direction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations